2023
DOI: 10.1108/lodj-08-2022-0356
|View full text |Cite
|
Sign up to set email alerts
|

The role of HEXACO in the development of authentic leadership and its consequences on task performance

Abstract: PurposeThe objectives of the current study were to identify the antecedents and outcomes of authentic leadership. For antecedents, the research considered the HEXACO (Honesty-Humility, Emotionality, eXtraversion, Agreeableness, Conscientiousness, Openness to Experience) personality model and thereby identified the impact of authentic leadership on employee performance with the mediating role of psychological safety and employee engagement by using the trait theory.Design/methodology/approachThe current study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 71 publications
0
19
0
Order By: Relevance
“…In their study, Malik et al (2023) found a significant relationship between Honesty–Humility and the development of authentic leadership (β = .094, p < .001). The findings are consistent with prior research (Malik et al, 2023).…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…In their study, Malik et al (2023) found a significant relationship between Honesty–Humility and the development of authentic leadership (β = .094, p < .001). The findings are consistent with prior research (Malik et al, 2023).…”
Section: Discussionmentioning
confidence: 89%
“…Hence, Agreeableness impacts Humble Leadership because such leaders are helpful to others (LaBouff et al, 2012). Malik et al (2023) found that agreeableness has significant impact on authentic leadership (b = .23, p \ .05). The current study results revealed that agreeableness is having 17% role in the development of humble leadership.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations